The Effect of Depth of Cut and Spindle Speed on Cutting Parallelism Results on Aluminum 6061 CNC TU-3A Retrofit Machine - Santosa, Salindra Sakti Putra; Mashudi, Imam (TRANSMISI, 2024)
Machining process is an important part of manufacturing to form and finish high-precision components. Milling is a commonly used technique, and the advancement of CNC technology has enabled precise and consistent production. This study evaluated the effect of spindle speed and depth of cut on the surface parallelism (µm) of aluminum 6061 using a TU-3A retrofit CNC milling machine. A quantitative experimental method with factorial design of experiments (DOE) was applied, testing spindle speeds of 600 RPM, 800 RPM, and 1000 RPM and depths of cut of 1.0 mm, 1.5 mm, and 2.0 mm, while maintaining constant feed rates of 48 mm/min, 64 mm/min, and 80 mm/min. The results showed that spindle speed had no significant impact on surface parallelism (µm) (P-value = 0.924), although higher speeds showed a trend of better results. In contrast, depth of cut significantly affects parallelism (µm) (P-value = 0.000), with greater depth improving surface quality (µm). In addition, the interaction between spindle speed and depth of cut is also significant (P-value = 0.002), indicating that the combination of higher spindle speed with lower depth of cut produces better results. These findings suggest optimal machining parameters to improve surface parallelism (µm) in aluminum milling operations.